Oral hygiene status of student with special needs at special educational needs and disabilities school: a cross-sectional study - Anggraini, Laelia Dwi; Ningrum, Valendriyani; Batsukh, Nomundari (Universitas Padjadjaran, 2025)
Introduction: Oral health is an important part of overall body health. Children with disabilities are at risk or have chronic physical, developmental, behavioral, or emotional conditions; therefore, they commonly require some assistance in maintaining their cleanliness, particularly oral hygiene. This study aims to determine oral hygiene status of students with special needs at special educational needs and disabilities school. Methods: This was a descriptive study with a cross-sectional design, using total sampling technique. The subjects were 36 students aged 10-28 years from Special Educational Needs and Disabilities (SEND) school. Data were collected using the Oral Hygiene Index Simplified (OHI-S) which are Simplified Debris Index (DI-S) and a Simplified Calculus Index (CI-S) index. Results: The students with disabilities at SEND school had an average OHI-S score of 1.6, with DI-S score of 1.7 and CI-S score of 1.5, which falls into the severe category. Conclusion: The oral hygiene of students with disabilities is generally in poor condition. It is necessary to enhance promotive and preventive efforts specifically for children at SEND school with disabilities to improve oral health.